G255(P) Iron overload in Paediatric Haematology and Oncology. (7th April 2014) - Corn, O; Gattens, M; Williams, D
Abstract : Iron overload has long been recognised as a complication associated with multiple blood transfusions in the thalassaemic population leading to damage to the myocardium, liver and endocrine system. However, there has been little research looking at the paediatric oncology population, who often also require a large number of supportive blood transfusions secondary to the myelosuppressive effects of chemotherapy and routine monitoring of transfusion volumes and ferritin levels has not been standard practice. In a retrospective pilot study to look at the issue of potential iron overload in oncology patients, we identified twenty-three patients on high-risk treatment protocols all who required frequent blood transfusions during treatment. Five of these had completed treatment several years previously. Demographics, ferritins paired with CRP and the number of blood transfusions received were obtained from our hospital records and local shared care hospitals were contacted to complete the data if needed. Patients with incomplete data or paired CRP >30 were excluded and a total of 11 patients' data were analysed for the 'On treatment' group and 4 for the 'Post Treatment Group'. The results show that many children receive frequent transfusions and have high serum ferritin levels, but are not undergoing regular monitoring. There was a clear correlation between the number of transfusions received and the serum ferritin levels (p < 0.001). The results for the 'Post-Treatment Group' suggest that in some patients ferritin levels remain elevated outside of the normal range for some years after the end of treatment. In conclusion, paediatric oncology patients receive a significant number of transfusions during therapy. While there are few guidelines on treatment and monitoring in this cohort, these patients are at additional risk of organ toxicity secondary to chemotherapy drugs. More information on the degree and duration of exposure to elevated iron levels resulting in organ damage is necessary to determine optimal management.